Healthy, affordable and climate-friendly diets in India. (March 2018) - Rao, Narasimha D.; Min, Jihoon; DeFries, Ruth; Ghosh-Jerath, Suparna; Valin, Hugo; Fanzo, Jess
Highlights: Urban micronutrient are higher than rural at similar incomes. More than two-third Indians lack sufficient zinc, iron or Vitamin A. Shifting from rice to wheat and coarse cereals improves nutrition and lowers GHG. Healthy diversified diets are possible within food budgets and with less GHG. Abstract: India has among the highest lost years of life from micronutrient deficiencies. We investigate what dietary shifts would eliminate protein, iron, zinc and Vitamin A deficiencies within households' food budgets and whether these shifts would be compatible with mitigating climate change. This analysis uses the National Sample Survey (2011–12) of consumption expenditure to calculate calorie, protein and the above micronutrient intake deficiencies and relate them to diets, income and location. We show that more than two-thirds of Indians consume insufficient micronutrients, particularly iron and Vitamin A, and to a lesser extent zinc. A greater proportion of urban households than rural households are deficient at all income levels and for all nutrients, with few exceptions. Deficiencies reduce with increasing income. Using constrained optimization, we find that households could overcome these nutrient deficiencies within their food budgets by diversifying their diets, particularly towards coarse cereals, pulses, and leafy vegetables, and away from rice. These dietary changes could reduce India's agricultural greenhouse gas (GHG) emissions by up to 25%. Current agricultural and food pricing policies may disincentivize these dietary shifts, particularly among the poor.